CONFLICT BETWEEN INDIVIDUALS AND GROUPS IN A CHANGING ORGANIZATION – A CONCEPTUAL REVIEW - Fuad Cholisi; Sri Mulyono (Jurnal Sosial Humaniora, 2025)
The traditional view sees conflict as something negative and destructive, and therefore should be avoided. Contradictorily, the human relations view holds that conflict is a natural and inevitable part of organizational process and operation, which is not necessarily a negative thing. If conflict is handled in a constructive manner, it can lead to positive outcomes. This essay aims to explore how an organizational change can result in conflict between individuals or groups, the nature of the arising conflict, and some proposed formulations for conflict resolution. Organizations apparently need to keep changing because they have to continue to adapt to the continually changing situation and environment. Whilst research works generally reveals that conflict resulting from an organizational change is unavoidable due to different individual interpretations of facts and differences in expectations, the source of organizational changes may include power and politics, organizational structures, cultural differences, and environmental change. No matter which view of conflict one holds, it is widely agreed that conflict needs to be resolved in order to improve the performance of the organization involved, and among the proposed strategies of managing conflicts are the nine formulations proposed by Mullins and the Thomas’s Model of Conflict-Handling Styles.